Liquid metal hybrid antibacterial hydrogel scaffolds from 3D printing for wound healing - Li, Jinbo; Wang, Yu; Fan, Lu; Wang, Xiaoju; Shang, Luoran; Zhang, Hongbo; Zhao, Yuanjin (Elsevier B.V., 2025)
Hydrogels patches hold significant promise for wound healing. Endeavors have been dedicated to the improvement of hydrogel patch functionalities, with the aim of achieving systematic wound management. Herein, we present liquid metal (LM) hybrid antibacterial hydrogel scaffolds for wound healing via the 3D printing strategy. Gelatin/gellan gum-based hydrogel ink is adopted for printing the scaffolds, with LM microdroplets integrated within. Due to the excellent photothermal responsiveness of LM microdroplets, the LM hybrid scaffolds can convert the received near infrared light energy into heat energy, demonstrating controllable antibacterial ability. In addition, vascular endothelial growth factor is introduced into the scaffolds, which can be sustainably released and play an angiogenesis role. In vivo animal experiments demonstrate that this hydrogel scaffolds can effectively assit wound closure by eradicating bacterial infection and promoting angiogenesis. Thus, we believe that the proposed LM hybrid hydrogel scaffolds show promising prospects in wound treatment.